2017
DOI: 10.3892/etm.2017.4753
|View full text |Cite
|
Sign up to set email alerts
|

Groove resection of pancreatic head in groove pancreatitis: A case report

Abstract: Groove pancreatitis (GP) is a rare type of chronic pancreatitis, which primarily affects the groove area of the pancreatic head. Surgery is considered as the ultimate method for GP if the symptoms are not improved by conservative or endoscopic treatments, and the Whipple technique is the common choice at present. The present study introduces a novel surgical procedure for GP, namely groove resection of pancreatic head (GRPH), in a 56-year-old male patient. To the best of our knowledge, this is the first report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
3
0
3
Order By: Relevance
“…PD is a candidate surgical operation for GP while it is the only and standard surgical option for carcinomas of the pancreatic head[11-14]. Different from malignant diseases, groove resection of the pancreatic head is also considered a candidate surgical operation for patients with symptomatic GP that require a surgical intervention[15]. Complete duodenal obstruction was an important and specific symptom in our case.…”
Section: Discussionmentioning
confidence: 97%
“…PD is a candidate surgical operation for GP while it is the only and standard surgical option for carcinomas of the pancreatic head[11-14]. Different from malignant diseases, groove resection of the pancreatic head is also considered a candidate surgical operation for patients with symptomatic GP that require a surgical intervention[15]. Complete duodenal obstruction was an important and specific symptom in our case.…”
Section: Discussionmentioning
confidence: 97%
“…A part of the procedure used, it is proved that surgery highly improves quality of life and contributes to pain cessation in 76% of cases [ 2 ]. Recently, Chunfu and al demonstrated that GRPH (Groove Resection of Pancreatic Head): a novel surgical procedure, which involved the resection of the groove area of the pancreas only, while the duodenum, common bile duct, main pancreatic duct and the majority of the pancreatic head were preserved, is a feasible and effective technique, and this procedure may be an alternative for the surgical treatment of GP without duodenal stenosis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Причинами роста показателей являлось увеличение числа пациентов с желчнокаменной болезнью [4] и сохраняющееся на высоком уровне употребление чистого алкоголя в России (от 10,1 до 18 литров на душу населения в год в разных регионах по данным статистического управления). В структуре хирургических операций при ПХП авторы используют резекционные, а при протоковой панкреатической гипертензии -декомпрессивные вмешательства [6,8,9,16,17]. При поражении головки поджелудочной железы предпочитается выполнение ее резекции с сохранением двенадцатиперстной кишки [16,17], при декомпрессивных операциях отдается предпочтение анастомозам в сравнении с эндоскопическим стентированием панкреатического протока [8].…”
Section: цельunclassified
“…В структуре хирургических операций при ПХП авторы используют резекционные, а при протоковой панкреатической гипертензии -декомпрессивные вмешательства [6,8,9,16,17]. При поражении головки поджелудочной железы предпочитается выполнение ее резекции с сохранением двенадцатиперстной кишки [16,17], при декомпрессивных операциях отдается предпочтение анастомозам в сравнении с эндоскопическим стентированием панкреатического протока [8]. Используемые в настоящее время в хирургической практике различные виды вмешательств при ПХП требуют тщательного анализа их исходов и оценки качества жизни оперированных пациентов в сравнительном аспекте.…”
Section: цельunclassified
See 1 more Smart Citation